Guidance Counseling Techniques Through Muhasabah Qur'an and It’s Implication For Altruism Attitudes - Khoiriyah, Dianing Arifatul; Mu’is, Abdul; Mukaffan (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This article aims to explain guidance and counseling techniques through muhasabah Qur'ani in strengthening children's empathy at the Madrasah Aliyah Negeri 03 Jember. The researcher used a case study approach. The research instrument is the researcher himself (key information) using data collection techniques, interviews, observation, and documentation. Data analysis uses three stages: data condensation, data display, description, and conclusion, by testing the validity of the data through data triangulation and dependability. The research results concluded that the initial process carried out by the school and guidance and counseling teachers was identifying the problems and needs that occurred to students. The second is to give an analogy with the stories in verse in the Koran. The third is group counseling. The group guidance implemented at the Madrasah Aliyah Negeri 03 Jember helps new students to be able to carry out teaching and learning activities optimally and to become students who excel, have good morals, and have faith and piety. In the theoretical framework above, it has been explained that children with muhasabah qur'ani counseling techniques can have a confident attitude, can control their emotions, can get along well with friends, are independent, successful in learning, are socially responsible and care about the environment.